Preterm and low birth weight as risk factors for infant delayed development - Anggraini Alam; Abdurachman Sukadi; Nelly Amalia Risan; Meita Dhamayanti (Indonesian Pediatric Society, 2008)
Background In developed countries, birth weight of less than1,500 g contributes in infant delayed development. It might bedifferent in developing countries.Objective This study aimed to determine whether preterm infantswith birth weight of 1,500 to 2,499 g are risk factors for delayeddevelopment at 7-10 months of age.Methods We analyzed singleton infants at 7-10 months ofcorrected age, born with birth weight of 1,500 to 2,499 grams,preterm-appropriate for gestational age (or LBW group), and at7-10 months of chronological age, born with birth weight >2,500g-term-appropriate for gestational (non-LBW group) in a hospital-based retrospective cohort study. Data were taken from medicalrecords in Hasan Sadikin Hospital, Bandung, from September2003 to May 2004. We excluded infants with major congenitalanomalies, hyaline membrane disease, assisted ventilation, orexchange transfusion. Multiple regression logistic analysis wasperformed for data analysis.Results The percentage of delayed development in LBW groupwas higher than in non-LBW group (17.1% vs. 1.6%). Logisticregression analysis revealed that low birth weight was a risk factorfor delayed development (RR=5.13, 95%Cl 1.55;16.96, P=0.007).Other biological risk factors for delayed development arehyperbilirubinemia (RR=3.32, 95%Cl 1.29;8.54, P=0.013) andsepsis (RR=2.74, 95%Cl 1.15;6.52, P=0.023).Conclusions Preterm-appropriate for gestational age with birthweight of 1,500 to 2,499 g are risk factors for infant delayeddevelopment after being adjusted to other biological risk factors.